INFLUENCE OF MASS ‘U’ FORM IN LINE UP FORMATION TOWARDS AIR MOVEMENT ON SUPPORTING THERMAL COMFORT IN OUTSIDE SPACE OF APARTMENT LANDMARK RESIDENCE, BANDUNG - Marcella (Jurnal Riset Arsitektur, 2019)
Abstract- Indonesia with the characteristics of tropical climate requires control in design to achieve thermal comfort both in outside space and inside space. One of the factors that can affect thermal comfort is the pattern of air movement and air velocity. Landmark Residence Apartment is one of the new apartments in Bandung, with mass ‘U’ form in line up of new partially awakened. The newly constructed 'U' mass formation forms the characteristic of the two different masses, the space side in the closed A mass with the characteristic of the centered space as well as the side in the open mass B. this apartment become an object of research to determine the factors of order and mass form to the characteristics of air movement as well as thermal comfort in the outside space as a space of activities in residents. The method used in this research is descriptive-quantitative with simulation software Flow Design to know the air movement and measurement of thermal comfort factor at the point of population and sample which have been determined. This thermal factor will be analyzed using CET Nomogram method, so it generates thermal comfort level in outer space which will be associated with order and mass form of apartment. By using analysis of air movement patterns and CET Nomogram, it is seen that thermal comfort level in the outside space Landmark Residence apartment is more affected by wind velocity. The mass 'U' form with the back to wind direction will produce high wind velocity on the outside space of the building's side, while on the inner side of the 'U' form will form the shadow of the wind and the pattern of turbulence air movement affecting the achievement of different thermal conditions. The 'U' mass sequence lined up can also cause air movement on the inner side of closed A mass not getting enough air movement compared to open mass B with better airflow pattern. The pattern of air movement on the inner side of mass A can be at any time higher when the wind velocity enters the gap between the masses.  Key Words: apartment, outside space, mass ‘U’ form in line up, air movement, thermal comfort.